Fiscal Year and Festive Effects on Market Price Movements: A Guide to Trading Strategies at Nepal Stock Exchange - Rajesh Gurung; Paritosh Subedi (Pravaha, 2024)
This study aims to provide evidence of stock price seasonality specifically within the context of commercial banks operating in Nepal. It employs descriptive and correlational analysis to investigate the new year and festive effects on the stock prices of commercial banks in Nepal. The seasonal indices in descriptive analysis illustrate the movement in stock prices during different periods, and the correlation analysis exhibits how prices among banks behave. The study utilizes the daily trading data for the period from 2015 to 2023. The analysis reveals significant effects in the stock prices of commercial banks in Nepal, particularly related to the start of fiscal Year (mid-July) and major festive seasons occurring during October and November. Banks exhibits a significant correlation and the seasonal indices of all banks show a positive relationship with both inflation and the NEPSE index. This research provides valuable insights for investors, academics, and stakeholders, enabling them to identify optimal stock buying and selling times, enhance market dynamics, and make informed decisions. The unique impact of fiscal and festive periods on price movements of domestic commercial banks, not previously explored in the existing literature, is the primary focus of this study.